Hyperhydrophilic three-dimensional crosslinked beads as an effective drug carrier in acidic medium: adsorption isotherm and kinetics appraisal - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (New Journal of Chemistry, 2015)
Conventional drug delivery materials are known to provide slow and low drug loading in aqueous medium due to the hydrophobic or less hydrophilic properties of the carrier. However, the present study explored the synthesis of cheaply available metals modified with a hyperhydrophilic polymer. Hyperhydrophilic three-dimensional crosslinked beads as a drug carrier were synthesized with desirable properties that substantially influence the polymer efficiency. These synthesized polymers were characterized for surface area, particle size, acid content and morphology, and the metal modification was evaluated to obtain an efficient polymer for drug adsorption in an acidic medium. Contact time, which significantly affects drug adsorption was comparatively evaluated using the cheaply available metals, cobalt and nickel. Interestingly, an adsorption study revealed that gradual drug loading occurs during the initial 12 h. Afterwards, adsorption increases steadily and then stabilizes. Furthermore, theoretical predictions of adsorption, including Langmuir adsorption isotherm and pseudo order kinetics, were also evaluated. Remarkably, polymer supported Co/Ni demonstrated 85 and 78% metoprolol drug adsorption, respectively, at an optimum pH of 3 after 24 h. Langmuir adsorption isotherm revealed monolayer adsorption on the polymer supported Co/Ni. Pseudo first and second order kinetics were also evaluated and demonstrated the adsorption mechanism and equilibrium adsorption capacity, respectively.

Highly interconnected porous monolithic and beaded polymers using high internal phase emulsion polymerization: tuning porous architecture through synthesis variables - Ponrathnam, Timothy; Behere, Isha; Ponrathnam, Surendra; Ingavle, Ganesh (Polymer International, 2023)
Open porous polymeric materials have gained popularity due to their exceptional properties and applications in tissue engineering scaffolds, drug delivery, enzyme immobilization and catalysis support. This study developed a novel two-stage approach to create networked, crosslinked poly(2-hydroxyethyl methacrylate-co-N,N'-methylenebisacrylamide) HEMA-MBA beads. The first part involves producing an oil-in-water-in-oil high internal phase emulsion (HIPE). This is followed by suspension polymerization using a redox initiator pair. In this study, a mixed surfactant combination with low and high hydrophilicity-lipophilicity balance surfactants was identified and successfully utilized to prepare a stable oil-in-water-in-oil HIPE. The effect of crosslinker concentration (i.e. crosslink density), surfactant concentration and monomer-to-porogen ratio on pore architecture and surface area were successfully evaluated. In addition, a new protocol was developed to synthesize HEMA-MBA monoliths using an oil-in-water HIPE method at ambient temperature using a redox initiator pair. The effect of crosslink density and oil phase on pore architecture and surface area was evaluated. Key variables affecting the morphology of porous HEMA-MBA beads and monoliths were identified and quantified, allowing future development of porous HEMA-based polymer beads and monoliths with tunable morphologies which are suitable for numerous applications, especially in the biomedical field. (c) 2022 Society of Industrial Chemistry.
Keywords: HIPE polymerization; porosity; porous polymers; redox polymerization; Suspension polymerization